2019
DOI: 10.1111/ggi.13801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a water‐based exercise program on disability prevention in older Japanese adults

Abstract: Aim: This study aimed to evaluate the potential preventive effects of a water-based exercise program on disability in community-dwelling older adults. Methods:The study design was a propensity score-matched retrospective study. Older adults were contacted through a mail survey carried out by City Hall, and those who scored ≥3 points on the physical domain of the Kihon Checklist were encouraged to participate in the water-based exercise program. The program consisted of aerobic and walking exercises in the wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…38 Prior research has demonstrated the effectiveness of CRA in different settings-for example, in the United States, 3 Europe, 43 Australia, 17 or Asia. 44 Moreover, PA modalities were as diverse as trekking, 45 cycling, 46 exergames, 47 dance, 11 tai chi, 12 or yoga. 48 However, we could not find studies investigating the effectiveness of CRA in older individuals living in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…38 Prior research has demonstrated the effectiveness of CRA in different settings-for example, in the United States, 3 Europe, 43 Australia, 17 or Asia. 44 Moreover, PA modalities were as diverse as trekking, 45 cycling, 46 exergames, 47 dance, 11 tai chi, 12 or yoga. 48 However, we could not find studies investigating the effectiveness of CRA in older individuals living in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%